Development of Guided Inquiry-Based Textbooks on Respiratory System Materials to Improve Critical Thinking Skills - Rafiqa, Rafiqa; Setyorini, Dwi; Afiat, Nurul (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aims to produce a product of teaching materials in the form of textbooks that are used in the biological learning process on the respiratory system material. The textbooks developed are expected to be in accordance with the needs of students, valid, effective and practical to improve students' critical thinking skills. The research method uses Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The trial was conducted on 30 students of class XI IPA 4 SMAN 5 Palu. The learning method used in applying the textbook product is guided inquiry. Assessment of effectiveness with pretest and posttest. The data collection methods used were validation, observation, questionnaires and tests, while the data analysis techniques used qualitative and quantitative descriptive analysis. Based on the validator's assessment with valid criteria, it is known that the guided inquiry-based human respiratory system textbook that has been developed has an average score of 88.68%. The textbook category developed was very effective on student learning outcomes, seen from the pretest score of 26.32 and posttest of 63.00 with an N-gain value of 0.76. The students' critical thinking ability in the pre-test was obtained 36 while the posttest was 86. Based on the N-gain criteria, namely high with interpretation with very critical critical thinking skills. Learning responses with guided inquiry-based textbooks make students feel interested, easy, up-to-date and easy to understand. The results of the research generally show that the guided inquiry textbooks on respiratory system materials are valid, practical and effective on student learning outcomes and critical thinking skills.